Designing Sales Information Systems in Global Utama Furniture Inc., Bandar Lampung - Ochi Marshella Febriani; Nursiyanto Nursiyanto; Indera Indera; Neni Purwati (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The development of information technology was able to facilitate the sale data processing in Global Utama Furniture Inc. Moreover, the information technology was also regarded as a promising medium in spreading valid information in the field of businesses. Global Utama Furniture Inc. was the private business entity engaged in manufacturing furniture. As a large company, the Global Utama Furniture Inc. should develop an adequate system that was used for promoting the data processing and others. The problem statement of this study was that 1) the sold products were displayed through the product catalogs so that the customers had to come directly to the place; 2) the process of searching and checking product sales data needed a long time; and, 3) the payment process and final report preparation were delayed. The objective of this study was designing the sales information systems through a website-based application used to provide software development solutions on the product sale transaction in Global Utama Furniture Inc and to store all data in a database system. The system development method used in this study was waterfall method. The programming language used in this study was Java and MYSQL databases. The other tools used in this study were DFD, relationships between tables, etc. This sale information system provides convenience in making product promotion and sale information so that the data were successfully storage through the systemKeyword        : Planning, Waterfall, Sales and Promotion